(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
European classical music represents an important part of world cultural heritage and plays a significant role in the aesthetic education of younger generations. The teaching of classical music in general education schools contributes to the development of students’ artistic taste, emotional sensitivity, creativity, and cultural awareness. This article discusses modern methods of teaching European classical music in schools and examines pedagogical approaches that enhance students’ engagement, understanding, and appreciation of classical musical works. Special attention is given to listening activities, performance-based learning, multimedia technologies, interdisciplinary connections, and student-centered teaching strategies.